Foveal Avascular Zone Area Analysis Using OCT Angiography After Pneumatic Retinopexy for Macula-Off Rhegmatogenous Retinal Detachment Repair. (September 2019) - Francisconi, Carolina L. M.; Kim, David Ta; Juncal, Verena; Qian, Jenny; Brosh, Koby; Wong, David T.; Giavedoni, Louis R.; Berger, Alan R.; Altomare, Filiberto; Muni, Rajeev H.
Purpose: Recent publications have reported that the deep capillary plexus (DCP) area of the foveal avascular zone (FAZ) is significantly larger in eyes following pars plana vitrectomy (PPV) for rhegmatogenous retinal detachment (RRD) repair when compared with controls. To the best of the authors' knowledge, there have been no publications on the evaluation of the macular microvasculature using optical coherence tomography angiography (OCTA) in post–pneumatic retinopexy (PnR) eyes. Therefore, the purpose of this study was to investigate FAZ-area changes following PnR. Methods: This retrospective cohort included 19 patients with macula-off RRD who underwent PnR repair. Each patient's fellow eye was used as a control. The FAZ area in the superficial capillary plexus and DCP was investigated with OCTA and the areas were measured by 2 masked graders. Results: Both superficial (PnR: 0.22 [0.16-0.35] vs control: 0.24 [0.18-0.34] mm 2 ; P = .715) and deep (PnR: 0.56 [0.51-0.76] vs control: 0.7 [0.59-0.89] mm 2 ; P = .105) FAZ areas were not significantly different between eyes. Conclusions: Our results suggest that the lack of FAZ-area enlargement after PnR repair may indicate that there is less ischemic damage to the retinal capillary plexus in the fovea when compared with that described in the literature for PPV. The PIVOT trial demonstrated that PnR is associated with superior visual acuity and less metamorphopsia when compared with PPV at 1 year. The results of the current study may provide insight into the potential advantages of PnR. Further studies are needed to elucidate how the macular microvasculature is affected after RRD and to clarify how the FAZ area changes following PnR and PPV.